PENGUJIAN KUALITAS WEBSITE RSIA NURAIDA BERDASARKAN DIMENSI ACCESSIBILITY, EXPERIENCE, MARKETING, DAN TECHNOLOGY - Ari Nurfikri; Supriadi Supriadi; Annisa Syafa Andira (Universitas Indonesia, 2021)
This study aims to determine the quality of the RSIA Nuraida webiste and the factors causing the dimension that has the lowest score. This study uses a mixed method with an explanatory sequential design. The quantitative phase is carried out by testing the quality of the RSIA Nuraida website using a nibbler, based on the dimensions of accessibility, experience, marketing and technology. The qualitative phase was carried out by in-depth interviews with managers and staff related to the factors causing the lowest score of the four dimensions. The results of this study indicate the accessibility dimension has a score of 8.9, the experience dimension has a score of 6.6, the marketing dimension has a score of 3.3 and the technology dimension has a score of 8.4. The factor that causes the marketing dimension to have the lowest score is the lack of involvement of the marketing team in managing the website at RSIA Nuraida.Keyword: Digital Marketing, Website, Nibbler